Phase Shifted and Level Shifted PWM Based Cascaded Multilevel Inverter Fed Induction Motor Drive (International Journal of Current Engineering and Technology, 2014)
The multilevel converter to achieve higher power is to use a series of power semiconductor switches with several lower voltage dc sources to perform the power conversion by synthesizing a staircase voltage waveform. Batteries can be used as the multiple dc voltage sources. This paper focus on phase shifted and level shifted pwm based cascaded multilevel inverter fed induction motor drive. It offer several advantages compared to the conventional 3-phase bridge inverter in terms of lower dv/dt stresses, lower electromagnetic interference, smaller rating and high efficiency. The proposed method has been designed an thirteen level cascaded multilevel inverter by using phase shifted and level shifted pulse width modulation technique and compare the Total harmonic distortion. The selected pattern has been exposed to give superior performance in total harmonics distortion. Simulation and experimental results confirm the feasibility of proposed method.
Keywords: Multilevel inverter, Cascaded H-bridges, Batteries, PWM Technique, Induction Motor, THD